Inventarisasi Mikrofungi Akuatik Pada Perairan Madong, Kota Tanjungpinang, Provinsi Kepulauan Riau - Apriadi, Tri; Panjaitan, Andreas Bona Christian (Universitas Jambi, 2019)
Inventory of aquatic microfungi diversity needs to be done as a new information about specific types found in certain waters. The objective of this study was to determine the diversity of aquatic microfungi in Madong waters, Tanjungpinang City, Riau Islands. Research on diversity of microfungi was carried out through survey methods at three stations (mangrove areas, fishing settlements and floating net cages, and coastal of Madong villages). Samples were collected by taking litters from the waters (roots, leaves, and branches of mangrove, and also seaweed). Isolation and culture process of aquatic microfungi were carried out in the laboratory. Microfungi isolates that were grown and were successfully identified were: Aspergillus sp., Epicoccum sp., Colletotrichum sp., Penicillium sp., and Stemphylium sp. Key words: aquatic microfungi, consortium, inventory, isolates, Tanjungpinang